ANALISIS PENGARUH CURRENT RATIO, TOTAL ASSETS TURNOVER, DAN HARGA SAHAM TERHADAP NILAI PERUSAHAAN PT. BAYAN RESOURCES, TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2022 - Cendrissa, Velencia Modenna; Tigor, Ryan Hasianda; Lestari, Deara Shinta (Jurnal Progresif Manajemen Bisnis, 2023)
This study aims to determine the effect of Current Ratio, Total Assets Turnover, and Stock Prices on Firm Value of PT. Bayan Resources, Tbk in 2013-2022. The data used in this study are the financial statements of PT. Bayan Resources, Tbk for the 2013-2022 period. Based on the results of the f test, Current Ratio, Total Assets Turnover, and Stock Prices have a simultaneous effect on the Firm Value of PT. Bayan Resources, Tbk in 2013-2022. Meanwhile, through the t-test, the Current Ratio with a test value of 0.005 < 0.05 has a negative and significant effect on the Firm Value of PT. Bayan Resources, Tbk in 2013-2022. Total Assets Turnover with a test value of 0.008 < 0.05 has a negative and significant effect on the Firm Value of PT. Bayan Resources, Tbk in 2013-2022. Stock prices with a test value of 0.015 < 0.05 has a positive and significant effect on the Firm Value of PT. Bayan Resources, Tbk in 2013-2022. In this study, the grand theory used is signal theory and efficient capital market theory. Simultaneously, all independents variable; Current Ratio, Total Assets Turnover, and Stock Prices contribution to explaining Firm Value which is proxied by PBV of 84.9%, while the remaining 15.1% is explained by other variables not examined or not included in this study.